Intercostal liposomal bupivacaine injection for rib fractures: A prospective randomized controlled trial. Issue 2 (February 2022) - Wallen, Taylor E.; Singer, Kathleen E.; Makley, Amy T.; Athota, Krishna P.; Janowak, Christopher F.; Hanseman, Dennis; Salvator, Ann; Droege, Molly E.; Strilka, Richard; Droege, Christopher A.; Goodman, Michael D.
Abstract : BACKGROUND: Blunt chest wall injury accounts for 15% of trauma admissions. Previous studies have shown that the number of rib fractures predicts inpatient opioid requirements, raising concerns for pharmacologic consequences, including hypotension, delirium, and opioid dependence. We hypothesized that intercostal injection of liposomal bupivacaine would reduce analgesia needs and improve spirometry metrics in trauma patients with rib fractures. METHODS: A prospective, double-blinded, randomized placebo-control study was conducted at a Level I trauma center as a Food and Drug Administration investigational new drug study. Enrollment criteria included patients 18 years or older admitted to the intensive care unit with blunt chest wall trauma who could not achieve greater than 50% goal inspiratory capacity. Patients were randomized to liposomal bupivacaine or saline injections in up to six intercostal spaces. Primary outcome was to examine pain scores and breakthrough pain medications for 96-hour duration. The secondary endpoint was to evaluate the effects of analgesia on pulmonary physiology. RESULTS: One hundred patients were enrolled, 50 per cohort, with similar demographics (Injury Severity Score, 17.9 bupivacaine 17.6 control) and comorbidities. Enrolled patients had a mean age of 60.5 years, and 47% were female. Rib fracture number, distribution, and targets for injection were similar between groups. While both groups displayed a decrease in opioid use over time, there was no change in mean daily pain scores. The bupivacaine group achieved higher incentive spirometry volumes over Days 1 and 2 (1095 mL, 1063 mL bupivacaine vs. 900 mL, 866 mL control). Hospital and intensive care unit lengths of stay were similar and there were no differences in postinjection pneumonia, use of epidural catheters or adverse events bet ween groups. CONCLUSION: While intercostal liposomal bupivacaine injection is a safe method for rib fracture-related analgesia, it was not effective in reducing pain scores, opioid requirements, or hospital length of stay. Bupivacaine injection transiently improved incentive spirometry volumes, but without a reduction in the development of pneumonia. LEVEL OF EVIDENCE: Therapeutic/care management, Level II. Abstract : In this study, we investigated the use of liposomal bupivacaine intercostal injection in a blunt chest wall trauma cohort evaluating the overall analgesic needs and respiratory physiology of patients with and without liposomal bupivacaine injection.Supplemental digital content is available in the text.